STRATEGI COPING MAHASISWA DALAM MENYELESAIKAN TUGAS AKHIR DI MASA PANDEMI COVID-19 - Nita Astuti Suryana (Social Welfare Study Program, 2022)
Abstract. The emergence of the Covid-19 pandemic has changed various aspects of human life which has hampered all activities including education in Indonesia and urged the implementation of distance learning which has never been done simultaneously before. The impact of the Covid-19 pandemic on final year students can also trigger stress. So, in dealing with perceived stress, an individual will carry out coping as an effort to reduce demands or eliminate perceived stressful situations. One of the coping used is by final year students of the Faculty of Social and Political Sciences, Padjadjaran University. The purpose of this study was to describe the coping strategies used by final year students during the thesis completion process during the Covid-19 pandemic which consisted of two dimensions and eight forms of coping strategies described by Lazarus and Folkman including; dimensions of problem focused coping namely planful problem solving, confrontative coping, and seeking for social support. And the emotion-focused coping namely positive reappraisal, accepting responsibility, self-controlling, distancing, and escape avoidance. The method used in this research is descriptive qualitative method with interview techniques and literature study. Keywords: Coping strategy, Stress, Final Year Students. Abstrak. Kemunculan pandemi Covid-19 telah mengubah berbagai aspek kehidupan manusia yang mengakibatkan seluruh kegiatan terhambat termasuk pendidikan di Indonesia dan mendesak diberlakukannya pembelajaran jarak jauh yang belum pernah dilakukan secara serempak sebelumnya. Adanya dampak pandemi Covid-19 bagi mahasiswa tingkat akhir juga dapat memicu terjadinya stress. Maka dalam mengatasi stress yang dirasakan, seorang individu akan melakukan strategi coping sebagai upaya dalam mengurangi tuntutan atau menghilangkan situasi stress yang dirasakan. Salah satu strategi coping yang dilakukan ini adalah oleh mahasiswa tingkat akhir Fakultas Ilmu Sosial dan Ilmu Politik Universitas Padjadjaran. Tujuan dari penelitian ini adalah untuk menggambarkan strategi coping yang digunakan oleh para mahasiswa tingkat akhir selama proses penyelesaian skripsi di masa pandemi Covid-19 yang terdiri dari dua dimensi dan delapan bentuk strategi coping yang dijelaskan oleh Lazarus dan Folkman diantaranya; dimensi problem focused coping yakni planful problem solving, confrontative coping, dan seeking for social support. Serta dimensi emotion-focused coping yakni positive reappraisal, accepting responsibility, self-controlling, distancing, dan escape avoidance. Metode yang digunakan dalam penelitian ini adalah metode kualitatif deskriptif dengan teknik wawancara dan studi pustaka. Kata kunci: Strategi coping, Stress, Mahasiswa Tingkat Akhir.